Spatial Dynamics and Economic Drivers of Paddy Field Conversion in South Minahasa Regency, North Sulawesi, Indonesia - Rotinsulu, Wiske Chriesti; Pakasi, Sandra Engelin; Waney, Nordy Fritsgerald Lucky (Sam Ratulangi University, 2026)
Cropped paddy fields threaten rice self-sufficiency and rural livelihoods in many parts of Indonesia. This study examines the spatial dynamics and economic drivers of paddy field conversion in South Minahasa Regency, North Sulawesi, focusing on Tumpaan and Tatapaan Districts. Spatial analysis of land-use data for 2019 and 2024 was combined with farm-level surveys of 30 farmers and comparative farm-budget analysis for irrigated rice and four alternative crops (melon, watermelon, chilli and patchouli). The results show substantial paddy field loss, with net reductions of approximately 160.749 ha in Tumpaan and 82.68 ha in Tatapaan over the study period. Farm-budget comparisons indicate that irrigated rice on 0.62 ha yields only a small positive net cash income, whereas melon and watermelon on 1 ha each and chilli on 0.60 ha generate very high net cash returns in the observed season; patchouli, by contrast, is clearly unprofitable. Farmer interviews highlight high production costs and low margins for rice, labour shortages, difficulties in accessing fertiliser, deteriorating irrigation infrastructure and attractive market opportunities for horticultural crops as key drivers of conversion. The findings suggest that paddy field protection policies will remain ineffective if they are not accompanied by measures that improve the profitability and reliability of rice farming while recognising farmers’ rational responses to income opportunities from alternative crops. Keywords: paddy field conversion; farm income; horticultural crops; spatial analysis